Dams as a mechanism to promote agricultural development in Algeria : Beni Haroun Dam and MEGA-PROJECT FOR WATERING in Mila as a Model - Daas, Ahmed (Journal of Human Sciences, 2020)
The study seeks to explain the role played by dams in Algeria to achieve agricultural development by focusing on the role played by water catchments, hydrographic basins to meet the needs of agricultural individuals, that the great importance of water today Due to droughts and precipitation due to the changing seasons and the phenomenon of global warming The study is based on the descriptive approach. The study was conducted by the Beni Haroun Dam in Mila In addition to the analytical approach, the study reached a group of results : the development of dams and hydrographic basins in Algeria is already leading to sustainable agricultural development and achieved self-sufficiency as the experience of Mila through the irrigation lands. construction, where the number of dams exploited in the east of Algeria is 32 dams, as well as more attention to agriculture due and suitable for agriculture not also exploited.